2020
DOI: 10.1038/s41598-020-63819-6
|View full text |Cite
|
Sign up to set email alerts
|

Elevated O-GlcNAcylation induces an antidepressant-like phenotype and decreased inhibitory transmission in medial prefrontal cortex

Abstract: Depression is a devastating mental disorder affected by multiple factors that can have genetic, environmental, or metabolic causes. Although previous studies have reported an association of dysregulated glucose metabolism with depression, its underlying mechanism remains elusive at the molecular level. A small percentage of glucose is converted into uridine diphosphate-Nacetylglucosamine (UDP-GlcNAc) via the hexosamine biosynthetic pathway, which serves as an immediate donor for protein O-GlcNAc modification. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Cortical neurons were prepared using a modified version of the technique reported by Cho et al [29]. Briefly, cells were collected from 18-day-old Sprague-Dawley rat fetuses.…”
Section: Cortical Neuron Culturesmentioning
confidence: 99%
“…Cortical neurons were prepared using a modified version of the technique reported by Cho et al [29]. Briefly, cells were collected from 18-day-old Sprague-Dawley rat fetuses.…”
Section: Cortical Neuron Culturesmentioning
confidence: 99%
“…UDP-GlcNAc serves as a donor molecule to transfer GlcNAc to proteins (O-GlcNAcylation). Within mouse PFC, levels of O-GlcNAcylation promote inhibitory synaptic transmission ( Cho et al 2020 ). This raises the question of whether O-GlcNAcylation contributes to the inhibitory action of volatile anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been observed that madecassoside improves cognitive function and synaptic plasticity in a mouse model of AD [ 125 ]. However, modulation of O-GlcNAcylation regulates autophagy in astrocytes and controls the antidepressant-like phenotype in neurons [ 126 , 127 ]. Gintonin has been used for the treatment or prevention of AD through elevation of hippocampal neurogenesis in APPswe/PSEN-1 double Tg mouse model of AD [ 122 ].…”
Section: Therapeutic Action Of App Triggered By Autophagymentioning
confidence: 99%